Contrasted seasonal balances in a Sahelian pastoral ecosystem result in a neutral annual carbon balance. (March 2019) - Assouma, Mohamed Habibou; Hiernaux, Pierre; Lecomte, Philippe; Ickowicz, Alexandre; Bernoux, Martial; Vayssières, Jonathan
Abstract: This paper explores an original approach in which greenhouse gas (GHG) emissions and carbon (C) accumulation are assessed monthly and at landscape scale to account for the highly seasonal monsoon climate and the mobility of pastoral herds that characterize West African pastoral ecosystems. The study was conducted in northern Senegal, in the service area of the Widou Thiengoly borehole, a circular zone of 706 km 2 centered on the borehole. The C balance was calculated using an ecosystem approach, i.e. taking all main sources of GHG emissions and C sinks of the ecosystem, not only anthropogenic sources, into account. The annual C balance of the pastoral ecosystem was −0.04 ± 0.01 tC-eq.ha −1 .year −1, showing that total GHG emissions were mitigated by C accumulation in trees, soil and livestock. The C balance varied considerably with the seasons, with a positive monthly balance in the wet season, from July to October (+0.58 tC-eq.ha −1 .month −1 ) and a negative monthly balance in the cold dry season from November to February and the hot dry season from March to June (−0.57 and −0.05 tC-eq.ha −1 .month −1 respectively). Care should be taken when generalizing these results, which were obtained in a dry year, because of strong inter-annual variations in rainfall. Highlights: Sahelian rangeland ecosystems have a neutral carbon balance. Accumulation of carbon and greenhouse gas emissions vary strongly between seasons. The main source of greenhouse gas emissions is livestock. The main carbon sinks are trees and soils. Seasonality is explained by both rainfall patterns and pastoral practices.